Cross-Subsidies, External Financing Constraints, and the Contribution of the Internal Capital Market to Firm Value - Billett, Matthew T.; Mauer, David C. (Review of Financial Studies, 2003)
We examine the link between the excess value of a diversified firm and the value of its internal capital market. Subsidies to small financially constrained segments with good relative investment opportunities significantly increase excess value, while transfers of resources from segments with good relative investment opportunities significantly decrease excess value. Of interest is that subsidies to small financially constrained segments with poor relative investment opportunities also significantly increase excess value. However, there is little evidence that this result depends on the diversity of a firm's investment opportunities. We conclude that financing constraints drive the relationship between the internal capital market and firm value.